Hindu worldviews: theories of self, ritual and reality - Frazier, Jessica (Bloomsbury Academic, 2017)
"Designed to help readers deepen their understanding of Hinduism, and reflecting themes central to the study of religion and culture, Jessica Frazier offers Hindu-culture based theories of self, ritual, community, the body, the cosmos and the sacred. Boxed case-studies from a wide number of Hindu texts provide readers with direct access to primary sources in translation, ranging from canonical texts and tantric cosmology, to devotional poetry. Hinduism is often depicted as being so diverse in its regional cultures, doctrinal forms and its history, that it is the most difficult of all of the world religions to understand, or for adherents to explain to others. Hindu Worldviews explains the practice and doctrines of Hinduism using western theoretical and philosophical concepts as a point of entry, connecting Hindu thought and practice directly with both western and Hindu theories. The breadth and diversity of Hinduism is addressed, with each chapter providing an interpretative paradigm to understanding the conceptual rationale behind Hindu ideas, texts, practices, and culture. Reflecting the typical themes and structure of Hinduism courses, Hindu Worldviews provides an accessible new perspective on both Hinduism and modern theory in the study of religion"--